OP0071 Tnf-Alpha, TNF Receptor, HLA-E and NKG2A Gene Polymorphisms and Response to Anti-TNF-Alpha Treatement in Rheumatoid Arthritis. (10th June 2014) - Swierkot, J.; Iwaszko, M.; Gebura, K.; Nowak, B.; Korman, L.; Kolossa, K.; Jeka, S.; Wiland, P.; Bogunia-Kubik, K.
Abstract : Background: Despite the fact that therapy with TNF-alpha inhibitors constitutes a breakthrough in rheumatoid arthritis (RA) management, no improvement is still achieved in approximately 30% of cases. Objectives: The aim of the study was to evaluate whether single nucleotide polymorphisms (SNPs) within the TNF-α and TNF receptor, and HLA-E and NKG2A receptor encoding genes affect the efficacy of therapy with TNF-α inhibitors in patients with RA. Methods: For these purpose 280 RA patients who had been treated with TNF-alpha inhibitors for at least 6 months or they stopped therapy because of adverse events were investigated and genotyped for 9 SNPs within the TNFA promoter (rs1800629 G>A; rs361525 G>A; rs1799724 C>T); TNF receptors ( TNFR1A : rs767455 G>A; TNFR1B : rs1061622; T>G) while 89 patients were studied for the HLA-E (rs1264457 C>T; HLA-E*01:01, HLA-E*01:03, A>G) and NKG2A (rs7301582 C>T; rs2734440 A>G) genes using LightSNiP typing or Custom TaqMan® SNP Genotyping Assays. Results: Among polymorphisms located within TNF-alpha and receptors genes only the TNFR1A (rs767455, G>A) and one of the TNFA (rs1799724, C>T) promoter polymorphisms were found to be associated with response to anti-TNF therapy. Significantly more patients with the homozygous TNFR1A AA genotype achieved a good EULAR response at 3 months compared to patients carrying the G allele (p=0.011). At week 24 DAS28 was significantly lower in patients homozygous for the TNFA T variant (DAS28 – 2.05) compared to the C allele carriers (p=0.045). As for HLA-E and NKG2A genes, after 3 months of anti-TNF treatment the significantly worse (EULAR DAS28) response was observed in patients carrying the HLA-E C allele (20/45 vs. 9/28, p=0.030), HLA-E*01:03/01:03 genotype (8/10 vs. 30/73, p=0.038), NKG2A- (rs7301582)- CC genotype (28/51 vs. 10/33, p=0.043) or NKG2A- (rs2734440)- AA genotype (15/26 vs. 15/50, p=0.026). At week 12 low disease activity or remission was not observed in any of the patients with the HLA-E CC genotype (p=0.09). Also treatment failure (inefficiency or loss of effectiveness of therapy) was more frequently observed in the HLA-E CC homozygous patients (5/8 vs. 12/61, p=0.018) as well as in those with the NKG2A- (rs2734440)- AA genotype (15/37 vs. 3/33, p=0.005). Conclusions: These results imply that the polymorphisms within genes coding for TNF-alpha and its TNFR1 receptor as well as HLA-E and NKG2A affect the response to anti-TNF therapy in patients with RA. Acknowledgements: Supported by the UMO-2012/05/N/NZ5/02607 and 2011/01/B/NZ5/05367 grants from the National Science Center. Disclosure of Interest: J. Swierkot Grant/research support: UMO-2012/05/N/NZ5/02607 and 2011/01/B/NZ5/05367, M. Iwaszko Grant/research support: UMO-2012/05/N/NZ5/02607 and 2011/01/B/NZ5/05367, K. Gebura Grant/research support: UMO-2012/05/N/NZ5/02607 and 2011/01/B/NZ5/05367, B. Nowak Grant/research support: UMO-2012/05/N/NZ5/02607 and 2011/01/B/NZ5/05367, L. Korman Grant/research support: UMO-2012/05/N/NZ5/02607 and 2011/01/B/NZ5/05367, K. Kolossa: None declared, S. Jeka: None declared, P. Wiland: None declared, K. Bogunia-Kubik Grant/research support: UMO-2012/05/N/NZ5/02607 and 2011/01/B/NZ5/05367 DOI: 10.1136/annrheumdis-2014-eular.5416